2022
DOI: 10.7759/cureus.21599
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the Musculoskeletal Pathological Processes in Post-knee Replacement Surgery With Osteopathic Manipulative Treatment: A Systematic Review

Abstract: Total knee arthroplasty (TKA) is a very common surgical treatment approach for severe osteoarthritis. Complications of TKA include loss of range of motion and prolonged analgesic requirement for pain control. Osteopathic manipulative techniques (OMT) have been utilized to address localized muscular stiffness to improve range of motion; however, limited studies directly correlate OMT and TKA recovery. This review highlights the therapeutic benefits OMT can have in the postoperative management of arthroplasty wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Viscerosomatic reflexes, in which visceral and somatic pain afferent nerve signals overlap in the dorsal horn and influence each other, can present as skin erythema for acute processes versus skin blanching for chronic states [ 12 ]. Depending on the area of these findings, different associations have been found to correlate between somatic findings and visceral pathology [ 13 - 16 ]. In this case, the appendix is associated with changes at thoracic level 12, which were missing on the structural exam.…”
Section: Discussionmentioning
confidence: 99%
“…Viscerosomatic reflexes, in which visceral and somatic pain afferent nerve signals overlap in the dorsal horn and influence each other, can present as skin erythema for acute processes versus skin blanching for chronic states [ 12 ]. Depending on the area of these findings, different associations have been found to correlate between somatic findings and visceral pathology [ 13 - 16 ]. In this case, the appendix is associated with changes at thoracic level 12, which were missing on the structural exam.…”
Section: Discussionmentioning
confidence: 99%
“…It may be applicable to apply the techniques and concepts from these chronic pain pathologies to the treatment of OA. A review that studied the effectiveness of OMT in total knee arthroplasty recovery following severe OA found manual lymphatic drainage with effleurage or lymphatic pump techniques helped control edema [ 11 ]. Effleurage and lymphatic pump techniques are indirect and passive modalities that improve lymphatic drainage through gentle or rhythmic pressure, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…The investigators argue that edema can mimic ischemia by creating a barrier that restricts blood flow due to the accumulation of inflammatory fluid. This optimized lymphatic drainage and blood flow then improves healing and reduces pain in the dysfunctional joint [ 11 ]. Table 2 presents the non-pharmacologic treatment of chronic knee pain syndromes.…”
Section: Reviewmentioning
confidence: 99%
“…A variety of different body systems and surgical techniques have been researched including musculoskeletal, cardiac, pulmonary, oncologic, and more [1,5,. These studies have demonstrated decreased symptoms at viscerosomatic levels of treatment [19,25], improved lymphatic circulation [37], improved cardiac function and perfusion [26], decreased length of hospital stay [11,14,29,35], decreased pain [20,21,24,28,29,31,32,34,36,38], decreased pain medication use [1,22,28,39] and decreased morbidity [29].…”
Section: Introductionmentioning
confidence: 99%